The Application of Moral Aspects to Pencak Silat Extracurricular Students at MIN 1 Bengkulu Tengah - Dolly Apriansyah; Roni Syaputra (Sinar Sport Journal, 2021)
This study aims to determine the application of moral aspects to students in extracurricular Pencak Silat at MIN 1 Bengkulu Tengah. This type of research is qualitative research. The population in this study were Pencak Silat Extracurricular Students at MIN 1 Bengkulu Tengah, totaling 14 students. While the sampling technique was carried out by the Total Sampling technique with a total sample of 14 students. Data were collected using participant observation and interviews. The results of the study, it can be concluded that a pencak silat athlete must have an aspect of morality (mental spiritual) which is a trait and attitude based on noble character, this has obligations: a) fear of God Almighty, b) tolerance, trust self-discipline and self-discipline, c) love for the nation and homeland, d) brotherhood of self-control, e) social responsibility. So the application of the moral aspect to pencak silat students at MIN 1 Benteng is good, this is shown based on the results of the study.